55.3k views
2 votes
H2+2h-120

The first 2 (one after H) is square

User Yooooomi
by
4.8k points

2 Answers

1 vote
h+12)⋅(h−10) because
See steps
Step by Step Solution:
More Icon
Reformatting the input :

Changes made to your input should not affect the solution:

(1): "h2" was replaced by "h^2".

STEP
1
:
Trying to factor by splitting the middle term

1.1 Factoring h2+2h-120
The first term is, h2 its coefficient is 1 .
The middle term is, +2h its coefficient is 2 .
The last term, "the constant", is -120

Step-1 : Multiply the coefficient of the first term by the constant 1 • -120 = -120

Step-2 : Find two factors of -120 whose sum equals the coefficient of the middle term, which is 2 .

-120 + 1 = -119
-60 + 2 = -58
-40 + 3 = -37
-30 + 4 = -26
-24 + 5 = -19
-20 + 6 = -14
-15 + 8 = -7
-12 + 10 = -2
-10 + 12 = 2 That's it

Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -10 and 12
h2 - 10h + 12h - 120

Step-4 : Add up the first 2 terms, pulling out like factors :
h • (h-10)
Add up the last 2 terms, pulling out common factors :
12 • (h-10)
Step-5 : Add up the four terms of step 4 :
(h+12) • (h-10)
Which is the desired factorization

Final result :
(h + 12) • (h - 10)
User Plus Ultra
by
4.2k points
4 votes

Answer:

(h + 12)(h - 10)

Explanation:

Assuming you require to factor the expression

Given

h² + 2h - 120

Consider the factors of the constant term (- 120) which sum to give the coefficient of the h- term (+ 2)

The factors are + 12 and - 10 , since

12 × - 10 = - 120 and 12 - 10 = + 2 , thus

h² + 2h - 120 = (h + 12)(h - 10) ← in factored form

User Marnix Harderwijk
by
5.0k points